Skulpturen. (Antwerpen : Galerie 9915, 1985)
Eerdekens, Fred ; Maes, Herman ; Kortekaas, Niek ; Dierickx, Guy ; Fierens, Kris ; De Backer, Jan
Skulpturen, Galerie 9915, Antwerpen, 21 juni tot 4 augustus en van 6 tot 22 september 1985
boek